Studi Perancangan Pembangkit Listrik Tenaga Surya (PLTS) Rooftop On-Grid di Gedung Rektorat Universitas Papua: Study on Design of Rooftop On-Grid Solar Power Plant at the Rectorate Building of Papua University - Roy Charly Workala; Antonius Duma Palintin; Jamius Bin Stepanus (Universitas Papua, 2022)
The demand for electrical energy needs is always projected to increase by 2,214 (TWh) in 2050 or an increase of 9 times compared to the previous years of 254.6 TWh, it's just that current energy needs are still dominated by non-renewable energy which has limitations and does not require energy. environmentally friendly. Therefore, renewable and environmentally friendly energy sources are needed. Utilization of solar energy which is converted into electrical energy is a solution to reduce the use of non-renewable energy. The average daily solar radiation in Indonesia is 4.8 kWh/m². The purpose of this research is to design PLTS Rooftop at the Rectorate Building of the Papua University using helioscope software and to analyze the estimation of electrical energy savings. In designing, using 198 Tallmax TSM-PD14 320 Wp solar modules, SMA Sunny Tripower 20000TL-US brand inverter with a capacity of 4 units (20kW) and an AC Combiner Box containing protective equipment. The simulation results show that the highest electricity production was in May at 8,031.50 kWh and the lowest was in February at 5,997.60 kWh. So from the calculation, the estimated average electrical energy savings is 18%